Impact of timing and severity of COVID-19 infection in pregnancy on intrauterine fetal growth- a registry-based study from Doha-Qatar - Fathima Minisha (16475100) (2023)
Background The novel coronavirus disease (COVID-19) pandemic has impacted pregnant women, increasing maternal and neonatal morbidity. The placenta is a potential target for the pathophysiological processes due to the increased thrombotic inflammatory activation and inadequate uteroplacental perfusion and oxygenation, potentially causing intrauterine growth restriction. This study investigates the impact of gestational age at diagnosis of COVID-19 and the presence of symptoms on intrauterine fetal growth in pregnant women. Methods A retrospective review of COVID-19 positive pregnant women in Qatar from March 2020 to March 2021 was conducted. They were divided based on trimester of pregnancy in which they were infected. The outcomes included birthweight, customised fetal birthweight centiles, small for gestational age (SGA) baby and daily growth increments, compared between the trimesters and between symptomatic and asymptomatic women. Results In our cohort, 218 women (20.5%) were infected in the first trimester, 399 (37.5%) in the second and 446 (42%) in the third. Women in the second trimester were significantly younger and symptomatic. Women infected in the first trimester were least likely to have diabetes. The mean birthweight,risk of SGA (11.5% vs 10% vs 14.6%, p=0.302), and median customized growth centiles (47.6% vs 45.9% vs 46.1%)were similar between the groups.. Symptomatic women had significantly lower mean birthweight (3147 gms vs 3222 gms) and median birthweight centiles (43.9% vs 54.0%)compared to the asymptomatic (p<0.05 for both). In women infected within 20 weeks of gestation, a delay in daily fetal growth increments was noted with symptomatic disease, although not statistically significant. Conclusion This study shows that women with symptomatic disease had lower birth centiles and birth weights. This was regardless of the gestational age at which they were infected. Early symptomatic disease seems to have an impact on fetal growth velocity; however, larger studies are needed to corroborate these findings.